PENGARUH PROFITABILITAS, LEVERAGE OPERASI, DAN UKURAN PERUSAHAAN TERHADAP PRAKTIK PERATAAN LABA - Adiningsih, Mia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to test the influence of profitability, operating leverage, and company sizeto the income smoothing practice at food and beverages companies which go public in Indonesia Stock Exchange.Based on the result of analysis it can be concluded that operating leverage has negative influence to the incomesmoothing practice since the sig value is 0.023 < (Î±) 0.05. The operating leverage has an influence to the incomesmoothing practice which means that operating leverage of food and beverages companies are relatively low andit indicates that the companies have conducted income smoothing since the companies have great liability. Thecompanyâs size has influence to the income smoothing practice because the sig value is 0.000 < (Î±) 0.05. Thecompanyâs size has influence to the income smoothing practice, it means that the bigger size of the company thebigger possibility to conduct income smoothing practice. The profitability has no influence to the incomesmoothing practice because its sig value is 0.252 > (Î±) 0.05. Profitability has no influence to the incomesmoothing practice since the companyâs profitability level is relatively high therefore the company can fulfilltheir needs from the profit which has been obtained. Therefore, the company tends to conduct income smoothingpractice.Keywords: profitability, operating leverages, companyâs size, and income smoothing